State Actions for Personnel Evaluation - Carol B. Furtwengler (Arizona State University, 1995)
This article is an analysis four major policy issues associated with state actions for personnel evaluation from 1983 to 1992 and provides descriptive information about state policy actions taken during those years. Twenty states enacted their first requirements for performance evaluation, and states assumed new roles for program development, implementation, and staff development. Twenty-nine states passed legislation for performance pay programs, but only five programs remained viable by 1992. States generally avoided the issue of teacher tenure when enacting legislation for teacher evaluation. Thirty-eight states enacted 67 changes in legislation prescribing specific requirements for personnel evaluation. During the early part of the reform movement, state actions focused on accountability; toward the end of the reform movement states actions relinquished control and returned responsibility for evaluation to local school districts. Legislation varied across the states in the purpose for evaluation: improvement, continuing employment, and performance pay. The study found a positive relationship (0.48) between state control over personnel evaluation and state funding of education.